Hearing Loss Preventions And Safety Of The Spinal Anaesthesia Which Performed At Two Different Levels - Cetin, Bilal; Saglam, Omer; Dursun, Engin; Karapinar, Ugur; Yondem, Omer Zuhtu; Aydemir, Baran (Asian Journal of Medical Research, 2015)
The effects on hearing of the spinal anesthesia which was performed at two different levels and safety of the procedures were examined.Forty patients at the ages between 20 and 33 without a previous hearing loss problem were divided into two groups which constituted of 20 individuals each. Spinal anesthesia was performed with 22 gauge Quinckle needles at the L4-L5 interspace in the first group, and at the L5-S1 interspace in the second group. The patients were hydrated with 500 cc saline solution during the intraoperative period, and with 2500 cc saline solution for a period of 24 hours postoperatively. The hearing thresholds were detected with a pure-tone audiometry on the pre and postoperative 1st, 2nd and 3rd days.Thirty-four patients were operated at the general surgery, and six at the urology clinics. The average age of the patients was 21.9. Any differences with respect to the hearing thresholds could not be demonstrated between the two groups.Spinal anesthesia is as a safe anesthetic technique which is currently being performed frequently. Despite the reports in the literature which claim that spinal anesthesia may cause hearing losses, no hearing losses occurred after the spinal anesthesia. In spite of these arguments, spinal anesthesia with a 22 G Quinckle spinal needle can be performed safely without any hearing loss. In our study as well as other studies, it is demonstrated that these hearing losses can be prevented by the pre- and post-operative hydration.